2010
DOI: 10.1111/j.1365-2036.2010.04436.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: the combination of rifaximin with partially hydrolysed guar gum is more effective than rifaximin alone in eradicating small intestinal bacterial overgrowth

Abstract: SUMMARY BackgroundAbnormal intestinal clearance is involved in the pathogenesis of small intestinal bacterial overgrowth (SIBO). It is known that partially hydrolysed guar gum affects intestinal motility. Eradication therapy of SIBO is based on antibiotic treatment: no data are available on the role of fibre supplementation in eradicating SIBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 40 publications
0
47
0
8
Order By: Relevance
“…Moroever, the prevalence of adverse events was significantly lower in patients receiving rifaximin in comparison with those receiving metronidazole. 22 Furnari et al 23 reported that 87% of patients treated with an oral antibiotic showed normal results of hydrogen breath tests. In a pilot study conducted by Khalighi et al 24 with the aim to evaluate the efficacy of a probiotic with lactic acid bacteria in the treatment of SIBO, patients receiving the probiotic demonstrated a better response than the control group (negative H 2 -breath test result in 93.3% of those receiving probiotic compared with 66.7% of the control group).…”
Section: Resultsmentioning
confidence: 99%
“…Moroever, the prevalence of adverse events was significantly lower in patients receiving rifaximin in comparison with those receiving metronidazole. 22 Furnari et al 23 reported that 87% of patients treated with an oral antibiotic showed normal results of hydrogen breath tests. In a pilot study conducted by Khalighi et al 24 with the aim to evaluate the efficacy of a probiotic with lactic acid bacteria in the treatment of SIBO, patients receiving the probiotic demonstrated a better response than the control group (negative H 2 -breath test result in 93.3% of those receiving probiotic compared with 66.7% of the control group).…”
Section: Resultsmentioning
confidence: 99%
“…There are several options, such as non-absorbable antibiotics and probiotics for the treatment of SIBO [14][15][16]. Although rifaximin has been used for the treatment of SIBO [21] and several studies have confirmed the clinical efficacy of rifaximin in patients with IBS [22,23], no study exploring the effects of rifaximin on the prevention and treatment of NSAID-induced small intestinal damage has yet been reported. The role of probiotics in the treatment of SIBO remains controversial.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with SIBO complain of similar symptoms to IBS and a proportion of IBS patients have notable symptoms relief after antibiotic therapy (20,21). At present, the diagnosis of SIBO is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, subjects were requested to eat a light dinner the day preceding the examination (21) and to fast until the examination. They were also asked to refrain from smoking and from physical activity the day before the test.…”
Section: Study Protocolmentioning
confidence: 99%